EvoKex at the SBFT 2024 Java Tool Competition - Sadykov, Rustam; Abdullin, Azat; Akhin, Marat (2024 IEEE/ACM International Workshop on Search-Based and Fuzz Testing (SBFT), 2024)
EvoKex is a test generation tool for Java that seamlessly integrates genetic testing from EvoSuite and concolic analysis from Kex. This integration is achieved through the dynamic sharing of states between these two powerful approaches. By combining genetic and concolic testing, EvoKex aims to overcome individual tools' limitations and provides a synergistic solution for enhanced automated test generation. This paper summarizes EvoKex's performance and experiences in the Java unit testing tool competition at the International Workshop on Search-Based and Fuzz Testing (SBFT) 2024.